A Clinicopathological Analysis of Molecular Subtypes of Breast Cancer using Immunohistochemical Surrogates: A 6-Year Institutional Experience from a Tertiary Cancer Center in North India - Somal, Puneet Kaur; Sancheti, Sankalp; Sharma, Aishwarya; Sali, Akash Pramod; Chaudhary, Debashish; Goel, Alok; Dora, Tapas Kumar; Brar, Rahat; Gulia, Ashish; Divatia, Jigeeshu (South Asian Journal of Cancer, 2023)
Objective Classification of breast cancer into different molecular subtypes has important prognostic and therapeutic implications. The immunohistochemistry surrogate classification has been advocated for this purpose. The primary objective of the present study was to assess the prevalence of the different molecular subtypes of invasive breast carcinoma and study the clinicopathological parameters in a tertiary care cancer center in rural North India.Materials and Methods All female patients diagnosed with invasive breast cancer and registered between January 1, 2015, and December 31, 2020, were included. Patients with bilateral cancer, missing information on HER2/ER/PR receptor status, absence of reflex FISH testing after an equivocal score on Her 2 IHC were excluded. The tumors were classified into different molecular subtypes based on IHC expression as follows-luminal A-like (ER- and PR-positive, Her2-negative, Ki67 < 20%), luminal B-like Her2-negative (ER-positive, Her2-negative and any one of the following Ki67% ≥ 20% or PR-negative/low, luminal B-like Her2-positive (ER- and HER2-positive, any Ki67, any PR), Her2-positive (ER- and PR-negative, Her2-positive) and TNBC (ER, PR, Her2-negative). Chi square test was used to compare the clinicopathological parameters between these subtypes.Results A total of 1,625 cases were included. Luminal B-like subtype was the most common (41.72%). The proportion of each subtype was luminal A (15.69%), luminal B Her2-negative (23.93%), luminal B Her2-positive (17.78%), Her2-positive (15.26%), TNBC (27.32%). Majority of the tumors were Grade 3 (75.81%). Nodal metastases were present in 59%. On subanalysis of the luminal type tumors without Her2 expression (luminal A-like and luminal B-like (Her2-negative), luminal A-like tumors presented significantly with a lower grade (p < 0.001) and more frequent node-negative disease in comparison to luminal B-like (Her2-negative) tumors. In comparison to other subtypes, TNBC tumors were more frequently seen in the premenopausal age group (p < 0.001) and presented with node-negative disease (p < 0.001).Conclusion This is one of the largest studies that enumerates the prevalence of various molecular subtypes of breast cancer in North India. Luminal B-like tumors were the most common followed by TNBC. TNBC tumors presented more commonly in premenopausal age group and with node negative disease in comparison to other subtypes.
Keywords: molecular subtypes; breast cancer; India; immunohistochemical surrogates; TNBC